Pengembangan Sistem Informasi Pembayaran berbasis Web pada Usaha TV Kabel (Studi Kasus: Linda Cable) - Thariq Al Astagis; Satrio Agung Wicaksono; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Linda Cable is a cable TV business located in Trenggalek which has 1400 active subscribers. Each month, Linda Cable charges a service bill that their customers must pay to the collection clerk. However, there are several problems that occur while recording the payments. Payments received by the collection clerks must be re-recorded by the administrator in the monthly report. Payment receipt are poorly managed and inefficient because of duplicated records. Linda Cable's payment business processes will be changed by allowing customers to choose between paying the bills themselves to the Linda Cable's office or being collected by collection clerk but with additional charges. This study aims to develop an information system that can help Linda Cable in recording payments, managing bills, generating billing slips and generating monthly reports. Waterfall method is used in this research to develop a web-based app. User acceptance test and validation test was performed due to ensure the developed systems has fulfilled the user requirements.